PERBEDAAN KADAR VITAMIN C DAN LAMA FERMENTASI TERHADAP YOGHURT DENGAN PENAMBAHAN SARI BUAH SIRSAK (ANNONA MURICATA L) - Palijama Putri Selibata; Alwi Smith; H Sinay (BIOPENDIX, 2017)
Background: Yogurt has a higher nutritional value than fresh milk because of the increase in total solids, so that the content of other nutrients also increases. In addition, yogurt is suitable for people with lactose intolerance or who are intolerant of lactose. One part of the soursop plant that can be used as medicine is fruit. Soursop fruit contains vitamins, dietary fiber, and antioxidant compounds that can function as compounds that can delay, slow down and prevent lipid oxidation. Method: This study was conducted at the Basic Biology and Basic Chemistry Education Laboratory of the Faculty of Mathematics and Natural Sciences, Pattimura University. In this study the number of treatments was 4 with different concentrations, the control group, the addition of soursop juice 30 ml, 60 ml and 100 ml. Results: Research shows that the more the concentration of soursop juice is added, the higher the content of vitamin C produced in the cow's milk yogurt. Conclusion: Different amounts of yoghurt with the addition of soursop juice have different levels of vitamin C. The highest average vitamin C is found in yogurt with the addition of 100 ml of soursop juice.